FUNCTIONAL TRAINING ON ANKLE SPRAIN REHABILITATION IN SOCCER PLAYERS - Du,Xufeng (2022)
ABSTRACT Introduction An ankle sprain is a common soccer injury. Functional training is used to rehabilitate muscle strength with undiscovered benefits on soccer players’ recovery. Objective Explore the functional training effects on ankle injury recovery in soccer players. Methods 29 amateur soccer players were randomly assigned to control (n=15) and experimental (n=14) groups with no statistical difference in age or sex (P>0.05). The experimental group used functional rehabilitation training, while the control group was treated with traditional rehabilitation methods. Both groups practiced 30 to 40 minutes of rehabilitation, three times a week, for two months. Mathematical statistics were used to analyze the effects of different injury rehabilitation on the two groups, estimating the ankle joint continuous motion angle by the tibialis anterior muscle electromyogram responses. Results The ankle instability assessment questionnaires were statistically different between the two groups of patients after rehabilitation training (P<0.05). There was a statistical difference in the agility test after the intervention. The ankle capacity score and agility test score were better in the experimental group (P<0.05). Conclusion Functional rehabilitation training can improve ankle performance after a sprain. This training can also help athletes avoid future sprains and is recommended as preventive training. Evidence Level II; Therapeutic Studies - Investigating the result.